midterm: done all except 2.1{a,d,f}
This commit is contained in:
parent
414b351bf0
commit
5026da324a
3 changed files with 54 additions and 8 deletions
|
@ -376,7 +376,7 @@ We first show that the lemma holds for $\tau \in [0,1]$. Since
|
|||
|
||||
$$\|\tilde{p}(\tau)\| = \|\tau p^U\| = \tau \|p^U\| \text{ for } \tau \in [0,1]$$
|
||||
|
||||
Then the norm of the step $\tilde{p}$ clearly increases monotonically as $\tau$
|
||||
Then the norm of the step $\tilde{p}$ clearly increases as $\tau$
|
||||
increases. For the second criterion, we compute the quadratic model for a
|
||||
generic $\tau \in [0,1]$:
|
||||
|
||||
|
@ -388,17 +388,18 @@ term in function
|
|||
of $\tau^2$ is negative and thus the model for an increasing $\tau \in [0,1]$
|
||||
decreases monotonically (to be precise quadratically).
|
||||
|
||||
Now we show that the monotonicity claims hold also for $\tau \in [1,2]$. We
|
||||
define a function $h(\alpha)$ (where $\alpha = \tau - 1$) with same monotonicity
|
||||
as $\|\tilde{p}(\tau)\|$ and we show that this function monotonically increases:
|
||||
Now we show that the two claims on gradients hold also for $\tau \in [1,2]$. We
|
||||
define a function $h(\alpha)$ (where $\alpha = \tau - 1$) with same gradient
|
||||
"sign"
|
||||
as $\|\tilde{p}(\tau)\|$ and we show that this function increases:
|
||||
|
||||
$$h(\alpha) = \frac12 \|\tilde{p}(1 - \alpha)\|^2 = \frac12 \|p^U + \alpha(p^B -
|
||||
p^U)\|^2 = \frac12 \|p^U\|^2 + \frac12 \alpha^2 \|p^B - p^U\|^2 + \alpha (p^U)^T
|
||||
(p^B - p^U)$$
|
||||
|
||||
We now take the derivative of $h(\alpha)$ and we show it is always positive,
|
||||
i.e. that $h(\alpha)$ has always positive gradient and thus that is it
|
||||
monotonically increasing w.r.t. $\alpha$:
|
||||
i.e. that $h(\alpha)$ has always positive gradient and thus that it is
|
||||
increasing w.r.t. $\alpha$:
|
||||
|
||||
$$h'(\alpha) = \alpha \|p^B - p^U\|^2 + (p^U)^T (p^B - p^U) \geq (p^U)^T (p^B - p^U)
|
||||
= \frac{g^Tg}{g^TBg}g^T\left(- \frac{g^Tg}{g^TBg}g + B^{-1}g\right) =$$$$= \|g\|^2
|
||||
|
@ -445,7 +446,50 @@ Which, since $B$ is symmetric, in turn is equivalent to writing:
|
|||
|
||||
$$g^T g \leq (g^TBg) (g^T B^{-1} g)$$
|
||||
|
||||
which is what we needed to show to prove that the first monotonicity constraint
|
||||
which is what we needed to show to prove that the first gradient constraint
|
||||
holds for $\tau \in [1,2]$.
|
||||
|
||||
**TBD**
|
||||
For the second constraint, we adopt a similar strategy as for before and we
|
||||
define a new function $\hat{h}(\alpha) = m(\tilde{p}(1 + \alpha))$, thus
|
||||
plugging the Dogleg step in the quadratic model:
|
||||
|
||||
$$\hat{h}(\alpha) = m(\tilde{p}(1+\alpha)) = f + g^T (p^U + \alpha (p^B - p^U)) +
|
||||
\frac12 (p^U + \alpha (p^B - p^U))^T B (p^U + \alpha (p^B - p^U)) = $$$$ =
|
||||
f + g^T p^U + \alpha g^T (p^B - p^U) + (p^U)^T B p^U + \frac12 \alpha (p^U)^T B
|
||||
(p^B - p^U) + \frac12 \alpha (p^B - p^U)^T B p^U + \frac12 \alpha^2
|
||||
(p^B - p^U)^T B (p^B - p^U)$$
|
||||
|
||||
We now derive $\hat{h}(\alpha)$:
|
||||
|
||||
$$\hat{h}'(\alpha) = g^T (p^B - p^U) + \frac12 (p^U)^T B (p^B - p^U) + \frac12
|
||||
(p^B - p^U)^T B p^U + \alpha (p^B - p^U)^T B (p^B - p^U) = $$$$
|
||||
= (p^B - p^U)^T g + \frac12 ((p^U)^T B (p^B - p^U))^T +
|
||||
\frac12 (p^B - p^U)^T B p^U + \alpha (p^B - p^U)^T B (p^B - p^U) = $$$$
|
||||
= (p^B - p^U)^T g + \frac12 (p^B - p^U) B^T (p^U)^T +
|
||||
\frac12 (p^B - p^U)^T B p^U + \alpha (p^B - p^U)^T B (p^B - p^U) = $$$$
|
||||
= (p^B - p^U)^T (g + \frac12 \cdot 2 \cdot B p^U) + \alpha (p^B - p^U)^T B
|
||||
(p^B - p^U) \leq $$$$
|
||||
\leq (p^B - p^U)^T(g + B p^U + B (p^B - p^U)) = $$$$
|
||||
=(p^B - p^U)^T(g+Bp^B) = 0$$
|
||||
|
||||
and we therefore obtain $\hat{h}(\alpha) \leq 0$, thus finding that the
|
||||
$m(\tilde{p})$ is indeed a decreasing function of $\tau$ or $\alpha = \tau - 1$
|
||||
also for $\tau \in [1,2]$, thus completing the proof for the lemma.
|
||||
|
||||
<!--
|
||||
$$\hat{h}'(\alpha) = g^T (p^B - p^U) + \frac12 (p^U)^T B (p^B - p^U) + \frac12
|
||||
(p^B - p^U)^T B p^U + \alpha (p^B - p^U)^T B (p^B - p^U) = $$$$
|
||||
|
||||
= (p^B - p^U)^T g + \frac12 ((p^U)^T B (p^B - p^U))^T +
|
||||
\frac12 (p^B - p^U)^T B p^U + \alpha (p^B - p^U)^T B (p^B - p^U) = $$$$
|
||||
|
||||
= (p^B - p^U)^T g + \frac12 (p^B - p^U) B^T (p^U)^T +
|
||||
\frac12 (p^B - p^U)^T B p^U + \alpha (p^B - p^U)^T B (p^B - p^U) = $$$$
|
||||
|
||||
= (p^B - p^U)^T (g + \frac12 \cdot 2 \cdot B p^U) + \alpha (p^B - p^U)^T B
|
||||
(p^B - p^U) \leq $$$$
|
||||
|
||||
\leq (p^B - p^U)^T(g + B p^U + B (p^B - p^U)) = $$$$
|
||||
|
||||
=(p^B - p^U)T(g+Bp^B) = 0$$
|
||||
-->
|
||||
|
|
Binary file not shown.
|
@ -1,3 +1,5 @@
|
|||
% Discussed with: Gianmarco De Vita (MATLAB solver for determining \tau)
|
||||
|
||||
function pk = dogleg(B, g, deltak)
|
||||
pnewton = - (B \ g);
|
||||
|
||||
|
|
Reference in a new issue